Postpartum behaviour as predictor of weight change from before pregnancy to one year postpartum - Seidell Jacob C; de Vries Jeanne H; van Poppel Mireille NM; Althuizen Ellen; van Mechelen Willem (BMC, 2011)
Abstract Background Postpartum weight retention affects many women and increases the risk of becoming overweight. The research objective was to study modifiable factors contributing to weight change at one year postpartum. Methods In this prospective cohort, postpartum behavior, such as physical activity, sedentary behavior, sleep, and intake of total energy, total fat and saturated fatty acids of 118 Dutch women were assessed in 2003/2004 by self-report at 6 weeks, 6 and 12 months postpartum. Mean postpartum scores were computed for the behavioral measures. In linear regression models it was determined which factors were associated with average weight change from before pregnancy to one year postpartum. Furthermore, factors associated with substantial postpartum weight retention (≥ 5 kg) were also studied in logistic regression models. Results At one year postpartum, the average weight of participants had increased by 0.9 kg (SD 4.4). Moreover, 20% of the women retained ≥ 5 kg. Women who perceived themselves more physically active than others were almost ten times less likely to retain ≥ 5 kg than women who perceived themselves equally active (OR = 0.11, 95%CI: 0.02 - 0.66). Exceeding the guideline for saturated fatty acid intake (OR = 3.40, 95%CI: 1.04 - 11.11), total gestational weight gain (OR = 1.14/kg, 95%CI: 1.01 - 1.27), and not having completed post high school education (OR = 5.13, 95%CI: 1.66 - 15.90) increased the odds of retaining ≥ 5 kg. Conclusions Since one in five women had substantial weight retention postpartum, effective interventions for the prevention of weight retention are much needed. Future studies should evaluate whether interventions focusing on the identified modifiable postpartum factors are successful in reducing weight retention after childbirth.